Internal Plate Fixation of Comminuted Fracture of the Distal End of the Tibia and Fibula Using a Single-Incision Technique: A Novel Approach and a Series of Nine Cases - Tej Pratap Gupta; Narender Singh; SK Rai; Vivek Mathew Philip; Ritesh Sharma (Journal of Orthopaedic Case Reports)
Introduction: Comminuted fractures of the distal end of the tibia and fibula usually occur due to high-velocity trauma, and the tibia, being subcutaneous in this area, is prone to wound healing risks and complications. Fixation typically involves two separate incisions, medial and lateral, which pose risks of wound healing complications and devascularization of the distal tibia. This study aims to present a novel single anterolateral incision approach for the internal fixation of distal tibia and fibula fractures to minimize soft-tissue complications. Case Report: Nine patients were treated with internal plate fixation for their comminuted fractures of the distal end of the tibia and fibula using a single-incision technique. The cohort included six male and three female patients, with a mean age of 31.8 years (range 17–59). Conclusion: We present nine cases of comminuted fractures of the distal end of the tibia and fibula treated with a single-incision technique for internal plate fixation, resulting in satisfactory outcomes without any wound healing complications.